EFFECT OF MINERAL COMPOSITION ON SEQUENTIAL EXTRACT OF LEAD AND CADMIUM IN SOME IRAQI SOILS - Abdul Baqi D.S. Al Maamouri; Salwa H. K. Al Shamary (The Iraqi Journal of Agricultural science)
This study was aimed to find out the effect of different soil components of some Iraqi soils under different climatic conditions and different parent materials on the adsorption of lead and cadmium. Soil samples were collected from four governorates (Dohuk, Wasit, Salah al-Din, and Basra), with three sites in each governorate, and two depths (0-30 and 31-60) cm. A chemical analysis of the soil were carried out to determine the amount of organic matter, carbonate minerals, total and crystallized free iron oxides. Results showed that the values ​​of and soluble and exchangeable lead binded with carbonate minerals, organic matter, oxides, and clay fraction in rates ranging between (0.27-1.04), (0.83-1.51), (18.81-41.58), (2.31-21.95), (3.93-23.75), and (5.65-5). 67.83)% respectively  of the soil content and the values ​​of the coefficient of determination R2 (0.86, 0.16, 0.72, 0.79, 0.40, and 0.69), respectively. As for the cadmium element, the results showed that its values ​​were (0.49-1.66), (1.13-2.47), (40.24-79.51), (0.24-7.98), (3.25-36.76) and (6.74-38.24)% for the soluble ,exchangeable and binded with carbonate minerals, organic matter, oxides, and clay fraction  respectively.